2021
DOI: 10.11591/ijai.v10.i3.pp735-742
|View full text |Cite
|
Sign up to set email alerts
|

Intrusion detection with deep learning on internet of things heterogeneous network

Abstract: The difficulty of the intrusion detection system in heterogeneous networks is significantly affected by devices, protocols, and services, thus the network becomes complex and difficult to identify. Deep learning is one algorithm that can classify data with high accuracy. In this research, we proposed deep learning to intrusion detection system identification methods in heterogeneous networks to increase detection accuracy. In this paper, we provide an overview of the proposed algorithm, with an initial experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…Supervised and unsupervised learning algorithms are used to produce increasingly higher levels of abstraction defined by the output properties of previous levels. Various methods are used in DL, such as deep belief networks (DBNs) [19], autoencoders [20], recurrent neural networks (RNNs) [21], long short-term memory networks (LSTMs) [22], and convolutional neural networks (CNNs) [13] [23][24]. This study proposes the use of a CNN for detection and segmentation methods in AR.…”
Section: Proposed Methods For Ar Using a Convolutional Neural Networkmentioning
confidence: 99%
“…Supervised and unsupervised learning algorithms are used to produce increasingly higher levels of abstraction defined by the output properties of previous levels. Various methods are used in DL, such as deep belief networks (DBNs) [19], autoencoders [20], recurrent neural networks (RNNs) [21], long short-term memory networks (LSTMs) [22], and convolutional neural networks (CNNs) [13] [23][24]. This study proposes the use of a CNN for detection and segmentation methods in AR.…”
Section: Proposed Methods For Ar Using a Convolutional Neural Networkmentioning
confidence: 99%
“…Deep learning is quite effective at dealing with such massive amounts of data and can generate highly accurate results. As a result, Internet of Things (IoT), big data analytics, and deep learning are all important to the growth of a high-tech society [22], [28], [74], [77], [89], [92], [93], [101], [103], [110], [114], [126], [149], [152], [155], [183], [188], [202], [232], [265], [318], [352].…”
Section: Big Data Analytics In Iotmentioning
confidence: 99%
“…They proposed a new migration learning method which linearly transforms the feature mapping of the target region, increases the weights of feature matching, enables knowledge transfer between heterogeneous networks, and adds discriminators based on adversarial principles to speed up feature mapping and learning [10]. Sharipuddin et al addressed the intrusion detection system in heterogeneous networks which is easily affected by objective factors such as devices and network protocols, proposed an identification method combining deep learning, and conducted preliminary experiments on denial-of-service attacks, and the experimental results showed that deep learning can improve the detection accuracy in heterogeneous networks [11]. Fu et al proposed a new model called Metapath Aggregation Graph Neural Network (MAGN) to improve the final performance.…”
Section: Related Workmentioning
confidence: 99%